IPA (IMPORTANCE PERFORMANCE ANALYSIS) AND CSI (CUSTOMER SATISFACTION INDEX) METHODS IN MEASURING THE QUALITY OF BANK SERVICES: EMPIRICAL EVIDENCE FROM BANK MUAMALAT MANADO BRANCH OFFICE - Azzochrah, Nurul Azizah; Muslihin, M. Azhar; Al’amri, Safira Salsabila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2022)
The quality of services in Islamic banking in minority areas greatly affects its ability to survive. This study aims to analyze the service quality of Bank Muamalat in Manado using the IPA (importance-performance analysis) and CSI (customer satisfaction index method) methods. The data sources in this study were Bank Muamalat Manado customers with a population of 2,000 customers and a sample of 95 Bank Muamalat Manado customers in 2018/2019 using data collection techniques through observation and questionnaires. The method used is a descriptive quantitative method, Cartesian interest-performance analysis using the Kolmogrov-Smirnov technique, and this data is processed using SPSS version 25. The results of this study indicate that the service quality at Bank Muamalat KC Manado is